Role of gut microbiota in infectious and inflammatory diseases - Maciel-Fiuza, Miriãn Ferrão; Muller, Guilherme Cerutti; Campos, Daniel Marques Stuart; do Socorro Silva Costa, Perpétua; Peruzzo, Juliano; Bonamigo, Renan Rangel; Veit, Tiago; Vianna, Fernanda Sales Luiz (Frontiers in Microbiology, 2023)
Thousands of microorganisms compose the human gut microbiota, fighting pathogens in infectious diseases and inhibiting or inducing inflammation in different immunological contexts. The gut microbiome is a dynamic and complex ecosystem that helps in the proliferation, growth, and differentiation of epithelial and immune cells to maintain intestinal homeostasis. Disorders that cause alteration of this microbiota lead to an imbalance in the host's immune regulation. Growing evidence supports that the gut microbial community is associated with the development and progression of different infectious and inflammatory diseases. Therefore, understanding the interaction between intestinal microbiota and the modulation of the host's immune system is fundamental to understanding the mechanisms involved in different pathologies, as well as for the search of new treatments. Here we review the main gut bacteria capable of impacting the immune response in different pathologies and we discuss the mechanisms by which this interaction between the immune system and the microbiota can alter disease outcomes.